Perfil epidemiológico dos pacientes atendidos no Centro de Referência em Implante Coclear do Hospital das Clínicas da Universidade Federal de Minas Gerais - Lilia Correia Simoes (2018)
Hearing loss can lead to serious impairments that affect language development, causing a reduction in the ability to communicate, difficulties in social interaction, and thus affect well-being and quality of life. Therefore, hearing loss has deserved special attention since it adversely affects the lives of individuals, especially those with severe and profound hearing loss. The degree of hearing loss and the age at which the diagnosis is made, as well as the intervention, act directly on the individual's overall development and cognitive and social capacity. In patients with profound sensorineural hearing loss, the cochlear reserve is insufficient for effective functional gain with auditory amplifiers. For these cases, the alternative is the cochlear implant. Cochlear implantation has been considered an effective resource, always accompanied by habilitation and / or auditory rehabilitation. Objective: To trace the epidemiological profile of the patients treated at the Cochlear Implant Reference Center of the Hospital das Clínicas of the Federal University of Minas Gerais. Methodology: This is a retrospective, observational, cross-sectional, study whose population will consist of patients seen at the Reference Center on Cochlear Implant from January 2010 to December 2016. For the accomplishment of this study data from the medical records of the patients will be collected and recorded pertaining to the chronological age, gender, municipality of residence, type, time of acquisition, degree and etiology of hearing loss, use of individual sound amplification devices, age of hearing loss detection and, for the implanted patients, data related to the type of cochlear implant, implanted ear, patient's age at the time of surgery, Computerized Tomography (CT) and Magnetic Nuclear Resonance (MRI) as well as speech-language pathology Results and Conclusions: The sample consisted of 374 patients attended at the HC-UFMG Reference Center on HF, of which 56% were female, with ages between 1 and 72 years old, average age 18.63 years and median of 8 eight years old, from the Municipality of Belo Horizonte and RMBH. Deep bilateral sensorineural hearing loss occurred in 86% of patients. The non-syndromic congenital etiologies of unknown causes were predominant. The implantation of the CI device was unilateral and performed mostly in patients aged 0 to 3 and in adults over 18, who underwent speech therapy prior to surgery. Regarding the reasons for contraindication to HF surgery, the most important was that they did not meet the speech-language criteria for HF indication.